Efficiency of Nitrification Inhibitor on Designing Nitrogen Fertilizer by Neem Compounds Based on Molecular Docking - Rahmadani, Kharmila; Manguntungi, Baso; Arwansyah, Arwansyah; Jumadi, Oslan; Khizbullah, Muhammad Aziz; Hidayat, Alfin; Ayunda, Nayeng Githa Aiyodya; Faiz, Muhammad; Vanggy, Leggina Rezzy; Septiawati, Ermin (Trends in Sciences, 2022)
In the agricultural trade, nitrogen fertilizer is one among the popular fertilizers within the world market. However, the high use of nitrogen fertilizers causes negative impacts within the type of environmental pollution, each in water, soil, and within the air. Nitrification inhibitor required to enhance the potency of nitrogen fertilizer use to realize additional economical production of food crops and minimize fertilizer related pollution of the environment. Neem (Azadirachta indica) act as an inhibitor nitrification that contained high tannin and the other secondary metabolite compounds. Neem plants encapsulated by urea as a nitrification inhibitor can increase nitrogen efficiency in the soil during fertilization. This research is a computational experiment research in solving problems using Molecular Docking Analysis. Molecular Docking method was performed using AutoDock Vina Tools 1.5.6 and Open Babel 2.4.1 Program. The use of molecular docking aims to predict ligand bonds and target proteins that focus on affinity and bond interactions. The high and low affinity of ligand-protein bonds is influenced by free bond energies, surface interactions, and intermolecular interactions. The results represent Neem (A. Indica) contains high tannin and the other secondary metabolite compounds (Nimbin, Nimbidin, Nimbic Acid, Nimbidinin, Nimbinin, Azadirachtin, Diepoxy Azadiradione, Dyhidrogedunin, Gallic Acid and Gedunin). Those metabolite compounds can inhibiting 4 enzymes such as methane monooxygenase, Hydroxylamine oxidoreductase, Nitric oxide reductase and Nitrite Reductase. From 10 metabolite compounds, Diepoxy Azadiradione and Gedunin may become the most stable complex that indicated become strength binding energy based on the lowest energy score of −10.3 kcal/mol. HIGHLIGHTS One of the agricultural problem is the inefficiency of Nitrogen fertilization will be released in the form of N2O and Nitrate gases which pollute the environment as a result of the nitrification process Azadirachta indica is known to have secondary metabolite which have the ability to inhibit nitrification The molecular docking method was used as an initial analysis of the effectiveness of secondary metabolites from Azadirachta indica inhibiting enzymes that play a role in the nitrification process GRAPHICAL ABSTRACT